Synthesis and Characterization of TiO2-CaO and TiO2-CaO-Fe2O3 Photocatalyst for Removal of Catechol - Tahya, Candra Yulius; Irawati, Wahyu; Karnelasatri, Karnelasatri; Purba, Friska Juliana (Molekul, 2019)
TiO2-CaO and TiO2-CaO-Fe2O3 photocatalysts have been synthesized through the surfactant-assisted sol-gel method. The catalysts were characterized using XRD, FTIR, SEM-ED Sand BET surface area. XRD pattern showed the formation of anatase TiO2 crystal phase both in TiO2-CaO and TiO2-CaO-Fe2O3. The TiO2-CaO has higher crystallinity than TiO2-CaO-Fe2O3. Based on the peak refinement using Rietveld, there are two peaks identified as Fe2O3 hematite in the sample TiO2-CaO-Fe2O3.  BET surface area analysis showed that the average pore size of TiO2-CaO and TiO2-CaO-Fe2O3 catalysts are 8.04 and 8.41 nm respectively, indicating both catalysts are mesoporous.FTIR spectra show that the vibration of Ti-O, Ca-O, and Ca-TiO2 were observed in both catalysts. SEM images confirm that both catalysts are porous material. The catechol removal using TiO2-CaO and TiO2-CaO-Fe2O3 improved with the increase of catalyst concentration. After 360 minutes of UV radiation, the removal of catechol using TiO2-CaO-Fe2O3 reached 46.0%, 48.3%, and 69.2%, while when using TiO2-CaO, it reached 22.1%, 36.8%, and 57.0% for 0.1 g, 0.15 g, and 0.2 g of catalysts, respectively. The photocatalytic activity of TiO2-CaO-Fe2O3 is not so strong compared to TiO2-CaO catalyst but the catechol adsorption property of TiO2-CaO-Fe2O3 is higher than that of TiO2-CaO catalyst.